PENGARUH ETNOSENTRISME KONSUMEN, PERSEPSI HARGA DAN KEMENARIKAN ATRIBUT TERHADAP SIKAP PRODUK DAN IMPLIKASINYA TERHADAP KEPUTUSAN PEMBELIAN DI INDONESIA - Kurnianto, Muhdi; Widiyanto, Ibnu (Faculty of Economics and Business Diponegoro University, 2015)
Polytron is one of the Indonesian electronic products that can survive among the many imported products on the market. Polytron needs to know the characteristics of Indonesian consumer ethnocentric to strengthen strategy and increase the use of local products. This study aims to determine whether the consumer ethnocentrism, perceived price and the attractiveness of Atribut affect the product attitude that have an impact on the purchase decision products. The samples used in this study were 150 people who have made a purchase Polytron product in Semarang. The questionnaire were distributed in June 2015 to July 2015. The data were then processed by using multiple regression analysis. The results showed that all three independent variables have positive and significant effect on the dependent variable. The atribute attractiveness affect the attitudes toward product. The attitudes toward product has a positive and significant influence on the purchase decision variable and acts as an intervening variable.